A New IoT Combined Face Detection of People by Using Computer Vision for Security Application - Aydin, Ilhan; Othman, Nashwan Adnan (Ieee, 2017)
In nowadays situation, the security forms the most important section of our lives. Security of the house or the near and dear ones is important to everybody. Home automation is an exciting area for security applications. This field has enhanced with new technologies such Internet of things (IoT). In IoT, every gadget behaves as a little part of an internet node and every node interact and communicate. Lately, security cameras are utilized in order to build safety places, homes, and cities. However, this technology needs a person who detects any problem in the frame taken from the camera. In this paper, an Internet of Things is joined with computer vision in order to detect the faces of people. For this purpose, to execute this system, a credit card size computer that utilizes its own camera board for the security system, such as raspberry pi 3 utilized. Likewise, Passive Infrared Sensor (PIR) mounted on the Raspberry PI is utilized to detect any movements. So it helps to monitor and get notifications when motion is identified, captures the image and detect the faces, then sends images to a Smartphone via utilizing telegram application. Internet of things based on telegram application used to see the activity and get notices when movement is detected.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: Face detection; Raspberry PI; Computer Vision; Internet of things; telegram